Dialektika Universalisme Dan Partikularisme Dalam Islam Perspektif Pendidikan Agama Islam - M Abdullah Viki; Sayyid Abdullah; Muhammad Hori (4, 2026)
The dialectic of universalism and particularism in Islam is a crucial issue in contemporary Islamic studies, particularly in the context of Islamic Religious Education (PAI), which faces the realities of a pluralistic and dynamic society. Islam embodies universal values ​​that transcend time and space, such as monotheism, justice, humanity, compassion, and the common good. However, in practice, Islamic teachings constantly interact with social, cultural, and historical contexts, giving rise to a variety of particular religious expressions. This study aims to analyze the dialectic between universalism and particularism in Islam and its implications for the development of the Islamic Religious Education paradigm. This study employed a qualitative approach with library research. Data sources were obtained from the Qur'an, Hadith, and the works of classical and contemporary Islamic scholars and thinkers relevant to the themes of universalism, particularism, and Islamic education. Data analysis was conducted descriptively and analytically using an interactive analysis model, encompassing data reduction, data presentation, and conclusion drawing. The study's findings indicate that universalism and particularism in Islam are not contradictory concepts, but rather dialectical and complementary. Universalism serves as the foundation for the values ​​and fundamental principles of Islamic teachings, while particularism provides a contextual framework for applying these values ​​to the social realities of students. From the perspective of Islamic Religious Education, this dialectic demands a critical, reflective, and dialogical pedagogical approach so that Islamic Religious Education (PAI) serves not only as a means of transferring knowledge but also as a process for developing a mature, moderate, and civilized religious awareness. Thus, Islamic Religious Education is expected to produce a generation of Muslims who are ritually devout, socially sensitive, tolerant, and committed to universal human values ​​in a pluralistic society. Abstrak Dialektika universalisme dan partikularisme dalam Islam merupakan isu penting dalam kajian keislaman kontemporer, terutama dalam konteks Pendidikan Agama Islam (PAI) yang dihadapkan pada realitas masyarakat yang plural dan dinamis. Islam membawa nilai-nilai universal yang bersifat lintas ruang dan waktu, seperti tauhid, keadilan, kemanusiaan, kasih sayang, dan kemaslahatan. Namun, dalam praktiknya, ajaran Islam selalu berinteraksi dengan konteks sosial, budaya, dan historis yang melahirkan beragam ekspresi keagamaan yang bersifat partikular. Penelitian ini bertujuan untuk menganalisis dialektika antara universalisme dan partikularisme dalam Islam serta implikasinya terhadap pengembangan paradigma Pendidikan Agama Islam. Penelitian ini menggunakan pendekatan kualitatif dengan jenis penelitian kepustakaan (library research). Sumber data diperoleh dari Al-Qur’an, Hadis, serta karya-karya ulama dan pemikir Islam klasik dan kontemporer yang relevan dengan tema universalisme, partikularisme, dan pendidikan Islam. Analisis data dilakukan secara deskriptif-analitis dengan menggunakan model analisis interaktif, meliputi reduksi data, penyajian data, serta penarikan kesimpulan. Hasil kajian menunjukkan bahwa universalisme dan partikularisme dalam Islam bukanlah dua konsep yang saling bertentangan, melainkan bersifat dialektis dan saling melengkapi. Universalisme berfungsi sebagai landasan nilai dan prinsip dasar ajaran Islam, sementara partikularisme menjadi ruang kontekstualisasi dalam penerapan nilai-nilai tersebut sesuai dengan realitas sosial peserta didik. Dalam perspektif Pendidikan Agama Islam, dialektika ini menuntut pendekatan pedagogis yang kritis, reflektif, dan dialogis agar PAI tidak hanya berfungsi sebagai sarana transfer pengetahuan, tetapi juga sebagai proses pembentukan kesadaran keagamaan yang dewasa, moderat, dan berkeadaban. Dengan demikian, Pendidikan Agama Islam diharapkan mampu melahirkan generasi Muslim yang taat secara ritual, memiliki kepekaan sosial, bersikap toleran, serta berkomitmen terhadap nilai-nilai kemanusiaan universal di tengah kehidupan masyarakat yang plural.